Principles of a healthy neighbourhood for sustainable development and social well-being: A review paper - Norainah Abdul Rahman; Pujiyanti, Indah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since the 1920s, the notion of a neighbourhood has been studied and implemented. Many modern neighbourhood concepts have been developed and implemented, including green, sustainable, liveable, quality, new urbanism, and safe, compact neighbourhoods. Recent advancements in the notion of neighbourhood are aimed at creating a healthy neighbourhood. As a result, this study undertakes a thorough review of the literature in order to synthesise existing framework knowledge in terms of healthy neighbourhood aims, elements, and principles, as well as the framework and model employed in prior research. From 1999 until the present, a search was conducted to collect only suitable models or frameworks in general, with the inclusion criteria of no time, global, and English language. The keywords healthy neighbourhood, liveable neighbourhood, and sustainable neighbourhood were found in 51 publications or journals. All titles and abstracts were evaluated for the aims, elements, and principles of a healthy neighbourhood in connection to sustainable development and social well-being. After filtering all relevant key terms, only 28 articles were discovered to be relevant and closed related in developing the conceptual framework for this study. Following a comprehensive check on the relevant phrases, this study used a snowball method to acquire the necessary publications. The prior theoretical and modelling paradigm was primarily concerned with sustainable development and social well-being. The researcher will employ three aspects and eight principles to create a complete conceptual framework for healthy neighbourhoods. The conceptual framework will be utilised and evaluated in the future for holistic healthy neighbourhoods.